Agencije kot institut upravnega prava - Pirnat, Rajko (Podjetje in delo, 2024)
The author argues that the special legal regulation of agencies as an institute of administrative law makes sense especially because of the independent regulatory agencies, since other forms of legal entities under public law are also applicable to other areas. The author sets out the rationale for the independence of regulatory agencies and describes the dimensions through which effective independence is ensured, as well as their accountability. Finally, he discusses the recent case of an attempt to influence the functioning of the Energy Agency with regard to the enforcement of the new network tariffs act, which is the most obvious example in recent times of an attempt to influence the independence of an agency.
Keywords: Upravno pravo